Impunity, human rights, and democracy : Chile and Argentina, 1990-2005 - Wright, Thomas C. (University of Texas Press, 2014)
Thomas C. Wright examines how persistent advocacy by domestic and international human rights groups, evolving legal environments, unanticipated events that impacted public opinion, and eventual changes in military leadership led to a situation unique in the world--the stripping of impunity not only from a select number of commanders of the repression but from all those involved in state terrorism in Chile and Argentina. This has resulted in trials conducted by national courts, without United Nations or executive branch direction, in which hundreds of former repressors have been convicted and many more are indicted or undergoing trial.